Pengaruh Green Intellectual Capital Terhadap Business Sustainability - Kezia Josephine; Bryan Alexander Ciptadi; Jason Aloysius (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
Economically, the company tries to make a profit as part of its natural motivation (business). Meanwhile, socially, the company must also have a beneficial impact on the community so that its existence gets social legitimacy. This study examines the effect of Green Intellectual Capital (GIC) on Business Sustainability (BS). In practice, green intellectual capital consists of Green Human Capital (GHC), Green Structural Capital (GSC), and Green Relational Capital (GRC) that reflects the intangible assets owned by the company including knowledge, wisdom, experience, and innovation with due regard to environmental welfare. This study uses 150 data samples of manufacturing companies in the period 2016-2018. Hypothesis testing uses SPSS statistical software version 24. The results of this study prove that only GHC and GRC have an influence on BS.